Exploring multicultural books through predictions and social interactions: A case study with kindergarteners in the United States. Issue 1 (March 2019) - Kim, So Jung; Wee, Su-Jeong; Park, Soyeon
Although previous studies have underlined the importance of social interactions, multicultural education, prediction/imagination, and bilingual/bi-literacy learning, the intersection of all these four areas is yet to be explored. This qualitative case study explored how young bilingual readers create meanings and develop literary responses through prediction, imagination, and social interaction while reading multicultural literature. As part of a larger longitudinal study, this study focused on kindergarten-age Korean-English bilingual children at a Korean Language School in a Midwestern city in the United States. The data were collected over five months using audio/video recordings, open-ended interviews, and children's artifacts. The findings suggest that creative participation and social interactions using two languages help young bilingual readers to engage deeply with the reading and encourage multiple perspectives.